The Drivers of Supply Chain Resilience in Developing Economy Tourism: Organizational Culture and Strategic Practices - Putranto, Diyan; Halawa, Fransiscus Amonio; Widodo, Rintis Eko; Setiawan, Fahmi; Ajizi , Budi Nurhamdani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This descriptive qualitative study addresses a critical theoretical gap by exploring the non-structural drivers of Supply Chain Resilience (SCR) within the highly vulnerable Tourism Supply Chain Management (TSCM) context of developing economies. Employing a multiple case study approach using in-depth interviews with expert decision-makers, the research aimed to uncover the cultural and strategic mechanisms enabling adaptive recovery. Thematic analysis identified three interconnected drivers of SCR: first, Strategic Foresight, which transforms conventional planning by actively integrating technological investments, such as AI and IoT, for predictive visibility and dynamic resource allocation; second, Organizational Culture, which serves as the core agility mechanism by fostering cross-functional collaboration and digital skills necessary for rapid service reconfiguration; and third, Localized Partnering Resilience, which relies on long-term relational assets and mutual trust but is critically reinforced by Verifiable Transparency technologies, such as Blockchain, to mitigate ethical governance risks and build consumer confidence. The study proposes a context-specific framework that positions Organizational Culture and Strategic Foresight as the critical antecedents to Supply Chain Agility, concluding that resilience in volatile markets is fundamentally a human and relational achievement. The findings offer specific, actionable recommendations for managers regarding governance and training, and for policymakers regarding integrated infrastructure and transparency standards.